Zero waste sugar refinery process: Mauritius experience - Anon (Universiti Malaysia Perlis, 2010)
Organized by Sustainable Development Unit Chancellery Department, Academic Management Division Deputy Vice Chancellor Office (Academic and International) Chancellery Department and School of Bioprocess Engineering, 1st November 2010 at Keikhlasan Hall, 10th Floor, KWSP Building, Kangar, Perlis.